PEMBERDAYAAN MELALUI PENDIDIKAN PERILAKU DAPAT MENINGKATKAN KEPATUHAN PENGOBATAN KLIEN DIABETES TIPE 2 - Supriadi, Supriadi; Kamil, Mutofa; Saripah, Iip; Parmudia, Joni Rahmat (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
Management of diabetes mellitus (DM) has been carried out through various government policies, but has not shown optimal results. The main obstacle is the low level of client compliance in treatment. The task of ensuring that DM clients comply with treatment is not only borne by health service providers, but clients are also responsible for this. This study aims to explore empowerment through behavioral education in helping type 2 DM clients adhere to treatment. This research uses quasi-experimental pre-test and post-test design without control methods. The sample was 15 people with inclusion criteria, namely type 2 DM clients, aged over 15 years, able to communicate and normal general condition. Data was collected through interview techniques using the Morisky Medication Adherence Scale 8 instrument. Data analysis used the T test. The results of the study showed that there was an influence of behavioral education on type 2 DM clients' compliance with treatment with p-value: 0.001. Empowerment through constructed behavioral education can help Type 2 DM clients comply with treatment, namely through changes in antecedents, behavior and consequences (ABC).